Effect of Doping Density and Parasitic Resistances on The Performance of Perovskite Solar Cells-based Graphene Oxide as Hole Transport Layer by SCAPS-1D - Fauji, Najmudin; Kardiman, Kardiman; Suci, Farradina Choria; Hakim, Muhammad Fahmi; Efelina, Vita; Widianto, Eri (POSITRON, 2024)
Perovskite solar cells (PSCs) have demonstrated remarkable improvement and promise to be produced as large-scale, low-cost devices. Several resistive losses, such as the loss current, the trapping, and the recombination of charge carriers, significantly inhibited the performance of PSCs. Typically, the series resistance (RS) and shunt resistance (RSH) of the devices influence these kinds of losses. In this study, we conduct a simulation analysis to investigate the effect of doping density and parasitic resistances (RS and RSH) on the performance of PSCs-based graphene oxide (GO) as a hole transport layer (HTL) using the SCAPS-1D. The doping density variations in HTL demonstrate improved power conversion efficiency (PCE) and fill factor (FF) as the doping density increases. Both RS and RSH significantly affect the PSC performance, as they control the shape and slopes of the current density (J-V) characteristic. The optimization method produced impressive results, including an open-circuit voltage of 0.94 V, a short-circuit current density of 22.51 mA.cmâˆ’2, a fill factor of 78.92%, and a power conversion efficiency of 16.75%. This study leads to a basic understanding of the physics of PSC devices. The proposed design provides a systematic analysis method for photovoltaic science and technology.